Respostas
respondido por:
1
An= a1 + ( n - 1 ) . r
An = 1 + (60 - 1 ) . 2
An= 1 + 59.2
An = 1 + 118
An = 119
O 60º termo é 119
Agora podemos calcular a soma dos termos da P.A
Sn = (A1 + An) . n
-------------------
2
Sn= (1 + 119) . 60
------------------
2
Sn = 120 . 60
------------
2
sn = 7200
--------
2
Sn= 3600
Então a soma dos 60 termos da P.A é 3600
An = 1 + (60 - 1 ) . 2
An= 1 + 59.2
An = 1 + 118
An = 119
O 60º termo é 119
Agora podemos calcular a soma dos termos da P.A
Sn = (A1 + An) . n
-------------------
2
Sn= (1 + 119) . 60
------------------
2
Sn = 120 . 60
------------
2
sn = 7200
--------
2
Sn= 3600
Então a soma dos 60 termos da P.A é 3600
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás